Wykorzystanie controllingu i rachunkowości zarządczej w małych przedsiębiorstwach - Dynowska, Joanna (The Usage of Instruments of Controlling and Management Accounting in Small Enterprises, 2006)
According to the survey concerning the system of controlling and management accounting, which was carried out in 20 firms with employment from 47 to 50 workers, most of the analyzed firms do not make use of the information coming from the system. This carries a risk of leading companies to invest in the wrong assets and to allocate resources in wrong products. It can also lead to making wrong decisions in income planning, optimal production plan, price policy, and whether or not to insource/outsource elements of the supply chain. Moreover, lack of experience in cost accounting results in defaulting mainly to absorption costing. Only a small percentage of companies implemented modem cost accounting techniques such as activity-based costing or target costing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 202-208